Cerebrospinal Fluid Lactate as a Prognostic Marker of Disease Severity and Mortality in Cryptococcal Meningitis - Abassi, Mahsa; Bangdiwala, Ananta S.; Nuwagira, Edwin; Tadeo, Kiiza Kandole; Okirwoth, Michael; Williams, Darlisha A.; Mpoza, Edward; Tugume, Lillian; Ssebambulidde, Kenneth; Hullsiek, Kathy Huppler; Musubire, Abdu K.; Muzoora, Conrad; et al. (Clinical Infectious Diseases, 2021)
Background: Cerebrospinal fluid (CSF) lactate levels can be used to differentiate between bacterial and viral meningitis. We measured CSF lactate in individuals with cryptococcal meningitis to determine its clinical significance. Methods: We measured point-of-care CSF lactate at the bedside of 319 Ugandan adults living with human immunodeficiency virus at diagnosis of cryptococcal meningitis. We summarized demographic variables and clinical characteristics by CSF lactate tertiles. We evaluated the association of CSF lactate with clinical characteristics and survival. Results: Individuals with high CSF lactate >5 mmol/L at cryptococcal diagnosis more likely presented with altered mental status (P < .0001), seizures (P = .0005), elevated intracranial opening pressure (P = .03), higher CSF white cells (P = .007), and lower CSF glucose (P = .0003) compared with those with mid-range (3.1 to 5 mmol/L) or low (≤3 mmol/L) CSF lactate levels. Two-week mortality was higher among individuals with high baseline CSF lactate >5 mmol/L (35%; 38 of 109) compared with individuals with mid-range (22%; 25 of 112) or low CSF lactate (9%; 9 of 97; P =<.0001). After multivariate adjustment, CSF lactate >5 mmol/L remained independently associated with excess mortality (adjusted hazard ratio = 3.41; 95% confidence interval, 1.55–7.51; P = .002). We found no correlation between baseline CSF lactate levels and blood capillary lactate levels. Conclusions: Baseline point-of-care CSF lactate levels are a prognostic marker of disease severity and mortality in cryptococcal meningitis. Individuals with an elevated baseline CSF lactate level are more likely to present with altered mental status, seizures, and elevated CSF opening pressure and are at a greater risk of death. Future studies are needed to determine targeted therapeutic management strategies in persons with high CSF lactate.
Keywords: Cryptococcal meningitis; Cerebrospinal fluid; Lactic acid; Prognostic marker; Mortality